Retinal Axon Interplay for Binocular Mapping - Fassier, Coralie; Nicol, Xavier (Frontiers in Neural Circuits, 2021)
In most mammals, retinal ganglion cell axons from each retina project to both sides of the brain. The segregation of ipsi and contralateral projections into eye-specific territories in their main brain targets – the dorso-lateral geniculate nucleus and the superior colliculus – is critical for the processing of visual information. The investigation of the developmental mechanisms contributing to the wiring of this binocular map in mammals identified competitive mechanisms between axons from each retina while interactions between axons from the same eye were challenging to explore. Studies in vertebrates lacking ipsilateral retinal projections demonstrated that competitive mechanisms also exist between axons from the same eye. The development of a genetic approach enabling the differential manipulation and labeling of neighboring retinal ganglion cells in a single mouse retina revealed that binocular map development does not only rely on axon competition, but also involves a cooperative interplay between axons to stabilize their terminal branches. These recent insights into the developmental mechanisms shaping retinal axon connectivity in the brain will be discussed here.